Molecular markers in vegetable improvement - Ansari, Abdul Majid (Horticultural Biotechnology Research, 2015)
Molecular markers directly reveal the polymorphism at the level of DNA. These are tags that can be used toÂ identify specific genes and locate them in relation to other genes. Genetic mapping of disease resistance genesÂ will help to improve the efficiency of plant breeding program, and it will lead to better understanding of theÂ molecular basis of resistance. However, it requires reliable pathological tests and polymorphic genetic markersÂ in a well-defined segregating population. Two strategies for developing markers for disease resistance genes are;Â the establishment of genetic maps with localization of major genes and quantitative trait locus; and targetingÂ particular regions. Marker-assisted selection (MAS) is an effective tool for enhancing selection procedure in aÂ breeding program. Therefore, MAS is using in the crop improvement program and also useful for the efficient selection of many resistance genes for pyramiding into a single genotype.